(untitled) (Sciences & Technologie. C, Biotechnologies, 2007)
Hyoscyamus albus L. is a medicinal plant pertaining to Solanaceae familly, it is rich mainly in tropanic alkaloids such as atropine and scopolamine. Plants of this specie were grown under controlled conditions, irrigated to half field capacity and treated with hormones, kinهtin (K) and 2,4-dichlorophenoxyacetic acid (2,4-D), at 0, 10 and 20 mg/l rates to follow the kinetic of alkaloids accumulation in the aerial and root parts. The results showed that spreading hormones increased alkaloids accumulation by a threefold rate estimated to be 1.98% in the aerial parts and by a fourfold rate estimated to be 1.55% in the root parts. The checks accumulated 0.73% and 0.38% for the two hormones cited in that order. A synergetic effect was observed between both hormones at higher applied rates (20 mg/l) on the measured traits and accumulated alkaloids compared to their separated effect. Hyoscyamus albus L. contains 5 alkaloids in the aerial and 6 the root parts. Ethanol was found to be the best solvent for the extraction of theses alkaloids.